2012
DOI: 10.2214/ajr.11.7634
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Value of Diffusion-Weighted Imaging in Combination With T2-Weighted Imaging in Diagnosing Prostate Carcinoma: A Systematic Review and Meta-Analysis

Abstract: T2WI combined with DWI may be a valuable tool for detecting prostate cancer in the overall evaluation of prostate cancer, compared with T2WI alone. High-quality prospective studies of T2WI combined with DWI to detect prostate carcinoma still need to be conducted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(88 citation statements)
references
References 41 publications
3
85
0
Order By: Relevance
“…A sensitivity of 55-88% and 46-90% and a specificity of 67-82% and 74-96% were reported by different authors for T2WI and DCE-MRI, respectively. [8][9][10] The introduction of diffusion-weighted imaging (DWI) by measurement of the restriction of water diffusion of suspicious lesions has significantly improved the detection and localization of PCa in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…A sensitivity of 55-88% and 46-90% and a specificity of 67-82% and 74-96% were reported by different authors for T2WI and DCE-MRI, respectively. [8][9][10] The introduction of diffusion-weighted imaging (DWI) by measurement of the restriction of water diffusion of suspicious lesions has significantly improved the detection and localization of PCa in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 12 systematic reviews [11][12][13][14][15][16][17][18][19][20][21][22] were relevant and met the preplanned inclusion criteria; however, none of them covered both of the guideline objectives or used the same study selection criteria as ours. A total of 8663 original studies in English were identified and 15 were analyzed.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…In a meta-analysis including a total of 698 patients with a previous negative prostate biopsy, the average sensitivity of DWI for detecting a carcinoma of the prostate is 38 % and the average specificity is 95 % [25]. The test quality parameters are slightly better for the combination of T2w images with DWI than for T2w images alone [26].…”
Section: Dwi Dce-mri 1 H-mrsmentioning
confidence: 96%
“…In MRI examinations with a field strength of 1.5 T, the application of a combined endorectal body phased-array coil is superior to the exclusive use of a phased-array coil without an endorectal coil with respect to image quality and local staging [26]. By using a combined endorectal body phased-array coil, the sensitivity and the positive predictive value for the detection of prostate cancer could be increased in individual studies even in 3 T MRI examinations [27].…”
Section: Endorectal Coilmentioning
confidence: 99%